Pemahaman Akuntansi, Motivasi Belajar, Kualitas Pengajaran Terhadap Prestasi Akademik - Prastyantini, Sri Lestari Yuli; mailinda, asri (Jambura Economic Education Journal, 2026)
The purpose of this study is to determine how accounting comprehension, learning motivation, and teaching quality can affect the academic achievement of accounting students in Yogyakarta. The research methodology used is quantitative with a causal associative approach. Data were collected by distributing questionnaires to 160 respondents who were accounting students from 11 universities in Yogyakarta. Data analysis was performed using SPSS version 25. The results showed that accounting comprehension, learning motivation, and teaching quality had a positive and significant effect on academic achievement, both partially and simultaneously. This indicates that the higher the level of accounting comprehension, learning motivation, and teaching quality received by students, the better their academic achievement. Thus, improving teaching quality and strengthening learning motivation are important factors in supporting the academic success of accounting students in higher education.